## 2x – 4 = -4 (x – 5)

### x = 4

To solve the equation 2x – 4 = -4(x – 5), we need to simplify both sides of the equation by expanding the brackets and collecting like terms.

Firstly, we will expand the brackets on the right side of the equation, using the distributive property of multiplication:

-4(x – 5) = -4x + 20

Now, the equation becomes:

2x – 4 = -4x + 20

Next, we will collect the like terms on both sides of the equation, which means we will group the x-terms on one side and the constant terms on the other side.

Adding 4x to both sides of the equation, we get:

2x + 4x – 4 = 20

Simplifying the left side of the equation, we get:

6x – 4 = 20

Adding 4 to both sides of the equation, we get:

6x = 24

Finally, dividing both sides by 6, we get:

x = 4

Therefore, the solution to the equation is x = 4. We can check this by substituting x = 4 back into the original equation:

2x – 4 = -4(x – 5)

2(4) – 4 = -4(4 – 5)

8 – 4 = -4(-1)

4 = 4

Since both sides of the equation are equal when x = 4, our solution is correct.

##### More Answers:

How To Solve For X: Step-By-Step Guide For The Equation 2(X+1)=6X-46Solve 2(3X + 1) = 7X – 5 With Step-By-Step Guidance

Learn How To Solve Equations: Step-By-Step Guide To Find The Solution To 3X = 2(7) + 2(5X)